Ultra structure of the denervated vocal muscle mechanically in hogs (sus scrofa domestica) - Leão, Henrique Zaquia; Pontes, Paulo Augusto de Lima; Coiro, Jose Rafael Rosito; Lamberts, Mariane (International Archives of Otorhinolaryngology, 2010)
Introduction: The literature is not clear in the ultra-structural manifestations of the vocal wrinkles after neural wound. Objective: To verify the alterations that occur in a vocal fold mechanically denervated. Method: In this prospective study, it were utilized 15 hogs of commercial race (Sus scrofa domesticates), with age of 4 to 12 weeks. The animals were distributed in three groups, chosen at random. Everybody was submitted to the denervation of the right vocal fold, with surgical removal of a segment with three centimeters of the recurring right laryngeal nerve. After 45, 90 and 180 days of the operations, it was proceeded the biopsy of the vocal muscles, it was prosecuted the samples for transmission electron microscopy and, for the ultra-structural study, utilized the transmission electron microscopy Philips, model EM208S. Results: The biopsied groups with 45 and 90 days after operation of mechanical denervation, presented disorganization miofibrilar, only vestigial lines Z in many samples, as well like altered mithochondrions presenting limited sizes, and matrix mithocondrial rarefied with rare mithocondrial cristae present. The biopsied group with 180 days after operation of denervation, presented regular sarcomeres, mithocondrions with sizes and regular number with correct positioning between the sarcomerical units. Conclusion: The finds in the ultra-structure of the vocal muscles suggest to re enervation of the muscle being that the muscular mithochondrions were the most sensible structures to the denervated condition, successions by the cytoarchiteture of the miofibrilas; the finds in the ultra-structure of the vocal muscles suggests to reinervation of the muscle in the period of approximately six months.